Effects of COVID-19 on Patient Safety Culture among Staff at a Teaching Hospital in Malaysia - Karthikayini, Krishnasamy; Mohd Idzwan, Zakaria; Tan, Maw Pin *; Karuthan, Chinna; Vairavan, Narayanan; Nazirah, Hasnan (Cambridge University Press, 2023)
Safety culture has been defined as "the product of individual and collective beliefs, values, attitudes, perceptions, competencies, and patterns of behavior of an organization's commitment to quality and patient safety by the Join Commission, 2017. The Coronavirus disease 2019 (COVID-19) which emerged in Wuhan, China, in December 2019, was subsequently declared a global pandemic by the World Health Organization led to unprecedented disruption to health-care systems worldwide. Shortages in supplies of personal protective equipment, particularly at the beginning of the pandemic have in fact led to health-care workers (HCWs) feeling unsupported and exposed to unnecessary dangers due to supply chain and raw material issues. The International Council of Nurses reported in 2020 that more than 260 nurses worldwide succumbed to COVID-19, raising the crucial issue of HCWs risking their lives to save the lives of others. This study was conducted to determine the potential changes in patient safety culture during the COVID-19 pandemic compared with the prepandemic levels at a tertiary hospital in a middle-income country in Southeast Asia.